Palpable Abdominal Masses in Indian Females: A Prospective Analysis - Ravinder Kumar; Madhu Digra (Dr. Annil Mahajan, 2023)
Background: The presentation of palpable abdominal masses (PAM) in females causes a diagnostic dilemma due to the possibility of varied origins from the gynaecological and non-gynaecological sources. In the current analysis, we focused on the evaluation of the risk factors associated with the diagnostic origin and the impact of the evaluation on therapeutic outcomes in females with PAM. Materials and Methods: Female participants were enrolled in gynaecology and surgery outpatient departments surgery. Analysis was performed to assess the risk factors related to the origin of PAM in the enrolled participants. Results: The study group included participants with PAM belonging to gynaecological origin (n=47) and non-gynaecological origin (n=33). No statistically significant difference was observed between participants with a gynaecological origin and non-gynaecological origin for PAM. In females with a gynaecological origin, the abdominal masses were observed more in the uterus and ovaries in comparison to the tubes. However, in the case of females with non-gynaecological origin, abdominal masses were observed more in the gastrointestinal tract and other places in comparison to the urinary tract. Conclusions: The present study highlights the need for including advanced imaging technologies supplemented with clinical history for a conclusive diagnosis and better choice of treatment.